MODIFIKASI MESIN MINI PEMECAH KULIT KACANG TANAH DENGAN MENGGUNAKAN PULLEY DAN V-BELT TIPE-B - Eko Prasetiyo; Indah Widanarti; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2021)
The existing peanut shell crusher machine can help peanut farmers in the process of breaking the peanut shell, but there are still a few obstacles in the process of breaking, namely the opening of the full opening stopper. This causes the peanut peeling machine to not operate optimally. The action to be taken is to modify the size of the B-type pulley and v-belt. Testing of the breaker machine that has been designed, uses peanuts with a moisture content of 5.60%. The test results show that for the 1/2 opening stopper, the yield produced is 68.8% in 45 seconds; 3/4 aperture, yield of 68.6% in 32 seconds of processing; and for full opening, the resulting yield is 71% in 20 seconds of processing time and obtain an effective tool performance capacity of 90 Kg/Hour.